POTENCY AND EFFICACY TEST OF A VACCINE IN ADDITION WITH ADJUVANT AGAINST KOI HERPESVIRUS IN KOI (Cyprinus carpio) - Lili Sholichah; Munti Yuhana; Angela Mariana Lusiastuti; Tri Heru Prihadi (Indonesian Aquaculture Journal, 2016)
Koi Herpesvirus (KHV) is a malignant virus infecting the goldfish and koi in all stadia and cause mortality up to 95%. The purpose of this study was to determine the potency and efficacy of inactivated-vaccine in addition with adjuvant against KHV in koi fish. The viral propagation was done using a KF-1 cell line in 25 cm3 flask. The cultured virus was harvested on 12 days post inoculation, and then the harvested virus was inactivated with 0.1% formalin as inactivated-vaccine. Three hundred of test fish (10.38 ± 1.25 g) maintained in 126 L of plastic containers with aeration, and fed with pellets twice a day. After 14 days of adaptation, the fish were divided into five treatments (A= vaccine; B= vaccine + Complete Freund’s Adjuvant; C= vaccine + Incomplete Freund’s Adjuvant; K+= positive control, and K-= negative control) and each treatment has four replicates. Vaccine was given by injecting intramuscularly of 0.1 mL per fish. All fish were challenged by injecting intramuscularly of 0.1 mL of KHV virus with concentration of 104.58 TCID50/mL after 21 days post vaccination. The results showed that the B treatment had higher (P<0.05) values of hematocrit level, lysozyme activity, and titer of antibody compared with positive control. In addition, the survival of fish in B treatment also had the highest percentages and significantly different compared to other treatments (P<0.05). The conclusion of this research was the application of inactivated KHV vaccine in 0.1% formalin with the addition of Complete Freund’s Adjuvant through the injection dose 0.1 mL fish-1 in 104.58 TCID50/mL capable to enhance the immune responses and raised the optimal protection of KHV antibody in koi fish.